2022
DOI: 10.1021/acs.chemmater.2c01474
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Fluorination of Disordered Rocksalt Cathodes through Rational Exploration of Synthesis Pathways

Abstract: We have designed and tested several synthesis routes targeting a highly fluorinated disordered rocksalt (DRX) cathode, Li 1.2 Mn 0.4 Ti 0.4 O 1.6 F 0.4 , with each route rationalized by thermochemical analysis. Precursor combinations were screened to raise the F chemical potential and avoid the formation of LiF, which inhibits fluorination of the targeted DRX phase. MnF 2 was used as a reactive source of F, and Li 6 MnO 4 , LiMnO 2 , and Li 2 Mn 0.33 Ti 0.66 O 3 were tested as alternative Li sources. Each synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 50 publications
(120 reference statements)
3
27
0
Order By: Relevance
“…Recent work has shown that LiF is highly volatile above its melting point (848 °C) when placed under flowing Ar. [ 27 ] This conclusion is further supported by the lower‐than‐stoichiometric amounts of Li detected in all LMTOF samples reported here (see ICP results in Table S2, Supporting Information). Notably, fluorination levels reported here are much lower than those previously reported for comparable DRX materials synthesized using a solid‐state approach (generally 2.5‐5 at%).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Recent work has shown that LiF is highly volatile above its melting point (848 °C) when placed under flowing Ar. [ 27 ] This conclusion is further supported by the lower‐than‐stoichiometric amounts of Li detected in all LMTOF samples reported here (see ICP results in Table S2, Supporting Information). Notably, fluorination levels reported here are much lower than those previously reported for comparable DRX materials synthesized using a solid‐state approach (generally 2.5‐5 at%).…”
Section: Resultssupporting
confidence: 76%
“…[12,[16][17][18][19][20][21][22][23][24][25][26] However, it remains challenging to synthesize DRX compositions with high fluorine content (>10%) using synthesis techniques that are scalable and can provide control over the particle morphology, warranting the exploration of alternate synthesis strategies. [27] DRX cathodes are typically synthesized via high temperature solid-state routes. [17,18,20,28,29] Although such routes often result in the desired DRX phase, they require that precursor powders are well mixed through mechanical mixing/milling to ensure a fast and homogenous reaction upon heating, and they provide poor control over particle morphology.…”
Section: Cation-disordered Rocksalt (Drx) Cathodes Have Recently Emer...mentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 In addition, F substitution at the oxygen site further improves the capacity retention and cycle stability by cation valency reduction, suggesting that fluorination is the key to maximizing performance. 10,24 Typically, these cathodes are synthesized by solid-state synthesis and Na−F as the only source of F. However, the dissociation energy of NaF is very high, such that its miscibility into metal oxides is very low when concentration is increased. In the case of cationdisordered rock salt (DRX) structures, fluorine preferentially incorporates into the cation-rich site (such as a Li-rich site), whereas this is severely hindered in ordered rock salt structures.…”
Section: ■ Introductionmentioning
confidence: 99%